2018
DOI: 10.1002/jcb.27427
|View full text |Cite
|
Sign up to set email alerts
|

DISC1 gene polymorphisms and the risk of schizophrenia in an Iranian population: A preliminary study

Abstract: Background: Schizophrenia, schizoaffective disorder, and bipolar illness are common psychological disorders with high heritability and variable phenotypes. The disrupted in schizophrenia 1 ( DISC1) gene, on chromosome 1q42, has an essential role in neurite outgrowth and cell signaling. The purpose of this study was to investigate the association of three single‐nucleotide polymorphisms (SNPs; rs6675281, rs2255340, and rs2738864) with schizophrenia disorder. These three SNPs were chosen as they had been used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…W skali świata rozpowszechnienie schizofrenii szacuje się na około 0,80% populacji w wieku powyżej 18. roku życia, co oznacza, że aktualnie żyje około 10 milionów ludzi z różnymi formami psychoz (Shokouhifar et al, 2018;Yang et al, 2016). W świetle przewidywanego wzrostu długości życia liczba ta podwoi się do roku 2030, a potroi -do 2050 (Toulopoulou et al, 2017).…”
Section: Wprowadzenieunclassified
“…W skali świata rozpowszechnienie schizofrenii szacuje się na około 0,80% populacji w wieku powyżej 18. roku życia, co oznacza, że aktualnie żyje około 10 milionów ludzi z różnymi formami psychoz (Shokouhifar et al, 2018;Yang et al, 2016). W świetle przewidywanego wzrostu długości życia liczba ta podwoi się do roku 2030, a potroi -do 2050 (Toulopoulou et al, 2017).…”
Section: Wprowadzenieunclassified
“…The disrupted‐in‐schizophrenia 1 (DISC1) gene was initially identified in a Scottish family with an unusually high prevalence of mental disorders, including schizophrenia, and the disruption was due to a balanced translocation of the chromosome (1:11) (q43, q21) (Millar et al., 2001). The DISC1 protein signaling pathway has been linked to multiple deficits in brain development both in humans and animals, which may lead to schizophrenia, bipolar disorder, recurrent major depression, and other neuropsychiatric disorders in humans, as well as phenotypical alterations reminiscent of human psychiatric disorders in animals (Austin et al., 2003; Clapcote et al., 2007; Hashimoto et al., 2006; Kirsty Millar et al., 2000; Shokouhifar et al., 2019). Recently, several studies have shown that the neural dysregulation caused by DISC1 impairs the Dopamine (DA) system by increasing the affinity of DA‐D2 receptors and increasing the removal of DA from the synaptic cleft because of translocation of the DA transporter, resulting in decreasing DA levels in the dorsal striatum, amygdala, and hippocampus (HPC, Hennah & Porteous, 2009; Ripke et al., 2014; Trossbach et al., 2016; Wang et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…DISC1 was originally identified in a Scottish family where chromosomal translocation directly disrupted brain-expressed genes associated with several psychological disorders, such as schizophrenia, bipolar disorder, and recurrent major depression (Millar et al, 2000; Blackwood et al, 2001). Alterations in the DISC1 gene are associated with impairments in brain development in humans, as well as primates and rodents, explicating a possible mechanism for their role in several psychiatric disorders (Austin et al, 2003; Hashimoto et al, 2006; Clapcote et al, 2007; Shokouhifar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%